Effects of orally administered clioquinol on the fecal microbiome of horses - Mikaila Z. Smith; Mary York; Kile S. Townsend; Lynn M. Martin; Tamara Gull; Lyndon M. Coghill; Aaron C. Ericsson; Philip J. Johnson (Journal of Veterinary Internal Medicine)
Abstract Background Whereas restoration of fecal consistency after treatment with clioquinol for chronic diarrhea and free fecal water syndrome has been attributed to its antiprotozoal properties, actions of clioquinol on the colonic bacterial microbiota have not been investigated. Objectives Characterize the dynamics of fecal microbial diversity before, during, and after PO administration of clioquinol to healthy horses. Study Design Experimental prospective cohort study using a single horse group. Methods Eight healthy adult horses received PO clioquinol (10 g, daily) for 7 days. Feces were obtained daily for 7 days before, during, and after conclusion of treatment, and again 3 months later. Libraries of 16S rRNA V4 region amplicons generated from fecal DNA were sequenced using the Illumina sequencing platform. Bioinformatic analysis was undertaken with QIIME2 and statistical analyses included analysis of variance (ANOVA) and permutational multivariate ANOVA (PERMANOVA). Results The richness and composition of the fecal microbiome was altered after administration of clioquinol, reaching a maximum effect by the fifth day of administration. Changes included a 90% decrease in richness, and compensatory expansion of facultative anaerobes including Streptococcaceae, Enterococcaceae, and Enterobacteriaceae. Multiple horses had Salmonella cultured from feces. Main Limitations Limitations including lack of control group and modest sample size are obviated by robust longitudinal study design and strong effect size associated with drug exposure. Conclusions Clioquinol has broad‐spectrum antibacterial effects on the fecal microbiome of horses, but spares certain bacterial families including several pathogens and pathobionts. Clioquinol should be used with caution in horses, in an environment free of contamination with fecal pathogens.